Soil-Landform Relationship to Understand Quantitative Pedogenesis under Varying Physiographic Catena of Chhotanagpur Plateau Regions of India - Siladitya Bandyopadhyay; Birendra Nath Ghosh; Samar Kumar Gangopadhyay; Krishnendu Das; Anil Kumar Sahoo; Subrata Mukhopadhyay; Jayjayanti Mukhopadhyay; Dulal Chandra Nayak (Journal of the Indian Society of Soil Science, 2023)
Pedogenic indices were considered to understand maturity of soils in different geomorphic units in quantitative terms. High redness rating and low sand/silt and silt/clay ratio at higher elevations of Rajmahal trap, Hazaribagh plateau and Ranchi plateau indicates rapid pedogenic processes and formation of Paleo- Alfisols (Rhodustalfs and Paleustalfs). High CEC/Clay in lower elevations of Rajmahal trap and Hazaribagh plateau indicates formation of more 2: 1 type of interstratified minerals. Predominant occurrence of amorphous iron (Fe) in soils of Rajmahal basalts was indicated by high ammonium oxalate extractable Fe. Higher proportions of dithionite extractable Fe of clay in gullied lands, uplands of Hazaribagh plateau and hillocks of Ranchi plateau indicate the prevalence of crystalline Fe in Chhotanagpur granite gneissic complex. More crystalline nature of soil clays at higher elevation of Ranchi and Hazaribagh plateaus are noted as indicator of laterization processes. Soils on pediments, uplands and plateaus comprise well matured profiles with formation of paleosols of relict types, whereas that of gullied lands and hillock were least weathered. Undulating plains, old alluvial plains and low-lying plains consists of soils under intermediate stages of weathering with intermediate stages of soil forming processes. These soils (P3, P4, P11 and P12) appear to support agricultural land use comparatively better than other soils despite topographic undulation and soil physicochemical constraints in the region. Presence of considerable amount of interstratified type of 2:1 minerals at lower elevations may attribute to restore better organic carbon sequestering capacity supporting long-term agricultural practices in the region. The present endeavour deals with study of quantitative pedogenesis as a tool to understand soil-landform relationship in varying physiographic catena of Chhotanagpur plateau regions of India.